An evaluation of the relationship between ethical leadership and employee performance - Mpye, Paul Motampe (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: The unethical conduct of higher education tertiary institution leaders influences organisational and individual employee performance. Employees in Technical and Vocational Education and Training (TVET) colleges have been victims of ineffective leadership styles. Therefore, the current study aimed to investigate the relationship between ethical leadership and employee performance in public sector TVET colleges in Gauteng Province, South Africa. Design/methodology/approach: The study was a quantitative research that employed a survey design to collect numerical data to test the research hypothesis. A simple random sampling technique was used to draw the study sample (n = 300 participants). A structured questionnaire was self-administered to employee participants to determine the existence of ethical leadership in their institutions and how the leadership style affected their performance. Findings: Research data was analysed statistically aided by the SPSS computer software to evaluate the influence of ethical leadership dimensions of employee performance. The research findings revealed that there is a statistically significant relationship between ethical leadership and employee performance in TVET colleges. Paper type: Research paper.